Expanding Horizon of English Language as a Lingua Franca - Bhandari, Sabindra Raj; Ghimire, Suman (THE ACADEMIA, 2025)
This article explores the growing influence of the English language in this world and how it has connected people of different linguistic backgrounds playing a significant role as a lingua franca. This study aims to show how the influence of English has increased as it has enabled global communication. It is expanding, reaching many people working as their medium of communication. It has also facilitated worldwide communication and cooperation, serving as a bridge language for communication. English as a communication medium in many international forums, business, academia, science, and technology has strengthened its use and continued its global status. Its dominance in digital content and programming language is likely to make it highly relevant in the future. With its extensive use, its hybrid and simplified version can be developed. It is also taught internationally and its promotion is also increasing even more with modern phenomena like migration, climate change, pandemics, international conflicts, and global challenges. It also has a chance to become a unanimous world language which can connect all the people of the universe including the threat of losing its present status of lingua franca. The article applies an explorative design to unveil how English from a small domain reached a larger arena.